PIC Simulations of the MS4 Thruster - Lewerentz, Lars; Kahnfeld, Daniel; Schulz, Niklas; Heidemann, Ralf; Schneider, Ralf (Frontiers in Physics, 2022)
Particle-in-Cell (PIC) simulations are used to model the MS4 test thruster of Thales Deutschland. Given as input the geometric shape, material components, magnetic field and the operating parameters of the experiment, the model is able to reproduce the experimentally observed emission pattern in the plume. This is determined by the magnetic field line structure and the resulting plasma dynamics in the near-field region close to the exit.